Agriculture and international trade : law, policy, and the WTO - Cardwell, Michael; Grossman, Margaret R.; Rodgers, C. P. [ (Christopher P.)] (Cambridge, Massachusetts : CABI Publishing, 2003)
This book addresses the interface between the law of international trade as it relates to agriculture, the emerging legal and economic order for agricultural trade under the auspices of the World Trade Organization (WTO), and their impact on agricultura policy reform in the EU and the USA. The book's particular focus is on key issues emerging in the Millennium Round of WTO negotiations, leading up to 2005 and the conclusion of new WTO agreements on agriculture and associated matters. The book has 12 chapters and a subject index.
1. The WTO, international trade and agricultural policy reform -- 2. The Uruguay Round agreement on agriculture and domestic support -- 3. The politics of agricultural trade -- 4. Farm subsidies and agricultural trade policy : the case of US support prorams -- 5. Multifunctionality and non trade concerns -- 6. Multifunctionality of agriculture : a European Community perspective -- 7. TRIPS and the protection of intellectual property in biotechnology in the United States -- 8. TRIPS, biotechnology, and the public domain : what role will world trade law play? -- 9. Regulating GM products in the EU : risk, precaution, and international trade -- 10. International trade in genetically altered agricultural products : impact of the biosafety protocol -- 11. Environmental policy and reform of European agriculture law -- 12. Reforming United States environmental regulations for agriculture : impediments and opportunities
Also available in electronic resource
Includes bibliographical references and index
Keywords: Agricultural laws and legislation; Free trade; Non-tariff trade barriers -- Law and legislation; Tariff on farm produce